PENGARUH PAD, DAU, DAN DAK TERHADAP BELANJA LANGSUNG - Ningsih, Rusiati; Wahidahwati, Wahidahwati (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis study is aimed to find out whether Local Own Source Revenue, General Allocation Fund and SpecialAllocation Funds give influence to the direct expenditure and the Surplus of Financing Budget and PopulationGrowth as the control variable. The research object is all districts / cities in East Java Province. The sampleshavebeen selected by using purposive sampling technique,so 35 Districts / Cities in East Java province which havemet the criteria have been selected as samples. The data analysis techniques have been done by using multiplelinear regressions analysis. Based on the results of analysis it shows that local own source revenue, Surplus ofFinancing Budgetand Population Growth give positive and significant influenceto the direct expenditure,General Allocation give significant and negative influenceto the direct expenditure, and Special Allocation Funddoes not give any influenceto the direct expenditure. The predictive ability of these five variables to the directexpenditure is 63.3% while the remaining 36.7% is explained by other variables which are not included in thisresearch.Keywords: Local Own Source Revenue, General Allocation Fund, Special Allocation Fund, Direct Expenditure